Analisis Teoritis Pengaruh ph terhadap Mobilitas Logam Berat dalam Tanah - Rusdiyah, Farda Hidayatul (Maliki Interdisciplinary Journal, 2024)
This theoretical analysis explores the impact of soil pH on the mobility of heavy metals, focusing on its influence on chemical reactions that determine the availability, mobility, and toxicity of heavy metals in the soil. Low pH (acidic conditions) generally increases the mobility of heavy metals like lead (Pb), cadmium (Cd), and zinc (Zn) by enhancing their solubility and reducing adsorption to soil particles. Conversely, higher pH (alkaline conditions) promotes the precipitation and strong adsorption of heavy metals, thereby limiting their mobility and decreasing environmental contamination risks. This paper also discusses the implications for soil remediation strategies and agricultural practices, highlighting how pH adjustments can be effectively utilized to manage heavy metal pollution. Future research should further explore these interactions to optimize remediation practices and ensure sustainable agriculture on contaminated lands.